ANALISIS KEMAMPUAN SISTEM IRIGASI TETES BERTINGKAT DALAM PEMBERIAN LENGAS TANAH PADA POLYBAG - I DEWA GEDE JAYA NEGARA; HUMAIROH SAIDAH; I WAYAN YASA; LILIK HANIFAH; DIANA PUSPITA DEWI (GANEC SWARA, 2022)
In increasing the supply of food in residential areas, it is necessary to encourage the use of land and water sources in the yard even though the land area is limited. The design of multilevel drip irrigation may be an option in these housings, and therefore it is necessary to test and determine the ability of the irrigation to discharge, uniformity and soil moisture produced. This study aims to determine the effect of using inch PVC pipe as a secondary network on discharge, uniformity (CU) and soil moisture (w) in a multilevel drip irrigation system. Experiments were carried out with a 150 liter reservoir water source 3 m high, soil moisture test with a test duration of 5 minutes, 10 minutes and 15 minutes. Data analysis was carried out on discharge data (Q), irrigation volume and soil moisture. The research results are presented in tables, graphs and concluded descriptively. The results showed that the secondary pipe flow rate was Q1 822.54 cm3/sec, Q2 107.47 cm3/sec and Q3 15.39 cm3/sec. Irrigation uniformity in TSK irrigation operations obtained CU of 72.67% and in SK obtained CU of about 51.49% to 89.34%. Soil moisture produced at a duration of 5 minutes, 10 minutes and 15 minutes with an initial soil moisture condition range of 14%-28%, the results on the 1st floor (w1) ranged from 41%-50%, for the second floor w2 it was around 31%-45 % and on the third floor w3 around 25%-40%